Microfilariae in a bone marrow aspirate - Tummidi, Santosh (BMC Res Notes, 2016)
BACKGROUND: Filariasis is a common cause of morbidity in certain parts of India, especially in the Coastal Districts. Repeated episodes of fever with chills and rigor, lymphadenopathy are the initial manifestations which gradually progress to elephantiasis. Wuchereria bancrofti is the most common parasite causing lymphatic filariasis in India. Detecting microfilaria in peripheral blood with or without Diethylcarbamazine citrate provocation is the common diagnostic modality in suspected cases. However microfilaria has been accidentally detected in fine needle aspirates, aspirated body fluids and even in bronchial washings. CASE PRESENTATION: We report a case of 65-year old female presented with back ache. On investigation she had leuco-erythroblastic blood picture in the peripheral smear and metastatic deposits in the bone marrow aspirate. W. bancrofti microfilariae was an incidental finding in the bone marrow aspirate. CONCLUSION: Finding of microfilariae in the bone marrow aspirate in the absence of clinical features of lymphatic filariasis is extremely uncommon and mostly are incidental findings. The peripheral blood may or may not reveal the microfilariae and eosinophilia in the peripheral blood is absent in majority of the cases. All the bone marrow aspirates must be screened for microfilariae in the endemic areas to identify the asymptomatic carriers.